KEBERHASILAN PELAYANAN REHABILITASI SOSIAL BAGI KORBAN PENYALAHGUNA NAPZA SUCCESS OF SOCIAL REHABILITATION SERVICES FOR VICTIMS OF DRUG ABUSE - suryani S (Media Informasi Penelitian Kesejahteraan Sosial, 2020)
abstract His study aims to determine the effectiveness of social rehabilitation services for victims of drug use. The location of the study was determined purposively, with consideration of the existing regional institutions / IPWL / social rehabilitation services that almost completed their rehabilitation period, for this reason the City of Pekan Baru Riau Province was determined (IPWL Lighthouse). The target of the research subject was determined purposively, male or female, as victims of drug abusers who were almost completely rehabilitated, then determined 30 residents. The object of the research is the effectiveness of social rehabilitation services for victims of drug abuse. Data collection techniques using interviews. Analysis of the data used is descriptive qualitative-interpretative. The results found social rehabilitation services for drug abusers victims (86.67%), there is still a 13.33 percent relapse rate, where the cause is association with peers, families do not want to accept and the community gives a negative stigma (excluded) Based on the above conclusions, it is recommended to the Indonesian Ministry of Social Affairs cq the Directorate of Social Rehabilitation of Drug Abuse Victims, for socialization to families and the community to be able to receive former residents back in their neighborhoods, further guidance is needed to monitor the progress of ex-residents through regular and ongoing visits.Keywords: Success - Social Rehabilitation - Drug Users abstrakPenelitian ini bertujuan mengetahui efektivitas pelayanan rehabilitasi sosial bagi korban pengguna Napza. Lokasi penelitian ditentukan secara purposive, dengan pertimbangan daerah yang ada lembaga/IPWL/layanan rehabiltasi sosial Napza yang hampir  menyelesaikan masa rehabilitasinya, untuk itu ditentukan Kota Pekan Baru Provinsi Riau (IPWL Mercusuar). Sasaran subjek penelitian ditentukan secara purposive, yaitu laki-laki atau perempuan, sebagai korban penyalahguna Napza yang hampir selesai direhabilitasi, maka ditentukan 30 residen. Sasaran objek penelitian adalah efektivitas pelayanan rehabilitasi sosial korban penyalahguna Napza. Teknik pengumpulan data menggunakan  wawancara. Analisis data yang digunakan adalah deskriptif kualitatif-interpretatif. Hasil penelitian ditemukan pelayanan rehabiltasi sosial penyalahguna Napza korban penyalahguna Napza efektif, (86,67%), masih ada tingkat relapse 13,33 persen, dimana penyebabnya adalah pergaulan dengan teman sebaya, keluarga tidak mau menerima serta masyarakat memberikan stigma yang negatif (dikucilkan) berdasarkan kesimpulan  di atas, direkomendasikani kepada Kementerian Sosial RI cq Direktorat Rehabilitasi Sosial Korban Penyalahguna Napza, untuk sosialisasi kepada keluarga dan  masyarakat agar bisa menerima kembali eks residen di lingkungannya, perlu bimbingan lanjut untuk memantau perkembangan eks residen  melalui kunjungan rutin dan berkelanjutan.Kata kunci: Keberhasilan –Rehabiliatsi Sosial –Pengguna Napza